Ways Of Developing Students’ Creative Thinking In Teaching Literary Texts (Journal of Pedagogical Inventions and Practices, 2026)
This article examines effective ways of developing students’ creative thinking in the process of teaching literary texts in primary education. The study emphasizes the importance of competency-based education, literary analysis, and creative approaches in “Mother Tongue and Reading Literacy” lessons. The author analyzes the role of textbooks, literary works, and educational tasks in fostering independent thinking, aesthetic perception, critical reflection, and creativity among students. Special attention is given to questions and assignments that encourage learners to interpret texts, express personal opinions, compare characters, create stories, and apply knowledge in practice. The article also highlights the significance of considering students’ age and psychological characteristics in literary analysis. Based on methodological and pedagogical sources, the paper concludes that properly designed text-based activities and creative tasks contribute to the formation of reading culture, literary competence, and students’ intellectual development.